Numerical Investigation of Double Diffusive Mixed Convection Laminar Flow in Two Sided Lid Driven Porous Cavity. Issue 4 (21st March 2014) - Agarwal, Lokesh; Satheesh, A.; Mohan, C.G.
<x xml:space="preserve">Abstract</x> This paper presents the numerical study of mixed convection in a two‐sided lid driven porous cavity due to temperature and concentration gradients. The top and bottom walls are stationary and insulated. The left and right walls are moving at an equal velocity (Vo) in the same direction. The temperature and concentration are kept high at the right wall and low at the left wall. The governing equations are discretized using finite volume method. The pressure–velocity coupling is performed by the SIMPLE algorithm. A third order differed QUICK scheme is applied at the inner nodes and a second order central difference scheme is used at the boundary nodes. The flow behavior and heat transfer are analyzed for different nondimensional numbers, such as, 1 × 10−4 ≤ Ri ≤ 10, 1 × 10−4 ≤ Da ≤ 0.1 and 0.7 < Pr < 10. The present numerical results are compared with the literature and are in good agreement. For the above selected nondimensional numbers, the heat and fluid flow behavior is investigated using local and average Nusselt (Nu) and Sherwood (Sh) numbers. Results show that the convection flow is significant up to Da = 0.1, beyond that the effect of porosity is negligible. The effect of Prandtl number (Pr) on average Nu is found to increase significantly.